High-purity composite rare earth monosilicate ceramic powder and preparation method thereof
Preparation of high-purity composite rare earth monosilicate (Yb2-xYx) SiO5 ceramic powder by sol-gel method, solving the problem of low powder purity and mismatch between thermal expansion in the prior art, and achieving efficient preparation and performance of the material The improvement provides technical support for high temperature corrosion and low thermal expansion for the new generation of aircraft engines.
Patent Information
- Application Number
- CN202411294152.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art (Yb2-xYx)SiO5 powders generally have problems such as low purity and mismatch between the surface material and the substrate thermal expansion coefficient, which is difficult to meet the requirements of high-temperature corrosion and low thermal expansion in new generation aircraft engines.
The high-purity composite rare earth monosilicate (Yb2-xYx) SiO5 ceramic powder was prepared by sol-gel method. The ytterbium nitrate pentahydrate, yttrium nitrate hexahydrate and ethyl tetrasilicate were weighed by stoichiometric ratio, and the temperature was heated and the temperature was constant. Stir to form a transparent precursor sol, which is subsequently dried and calcined to obtain a high purity (Yb2-xYx)SiO5 powder.
Achieve uniform distribution of rare earth elements, regulate the thermal expansion coefficient and thermal conductivity of the material, improve the thermal expansion matching and thermal insulation capacity of SiCf/SiC CMC with the coating material, and provide high stability for environmental barrier coatings in the engine thermal end components. and technical support for long-lived service.
Smart Images

Figure HDA0005045437650000011 
Figure HDA0005045437650000012 
Figure HDA0005045437650000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano material preparation, and in particular relates to a novel sol-gel method for preparing high-purity composite rare earth monosilicate (Yb 2-x Y x ) method of SiO5 ceramic powder. Background Art
[0002] As advanced aircraft engines develop towards high efficiency and high thrust-to-weight ratio, the surface temperature of their internal hot end components will far exceed the temperature range that traditional nickel-based high-temperature alloys can withstand. Silicon carbide fiber reinforced silicon carbide ceramic matrix composites (SiCf / SiC CMC) have the advantages of low density, high strength, high modulus, and oxidation resistance, becoming the most promising new thermal structural / functional material that can replace nickel-based high-temperature alloys. However, the actual service environment of the engine includes high temperature, corrosive media, gas scouring, and complex stress. Under the intertwined effects of these environmental factors, the performance of SiCf / SiC CMC continues to deteriorate, which seriously restricts its application in the hot end components of aircraft engines. Environmental barrier coatings (EBCs) technology is the key technology to ensure the long-term service of SiCf / SiC CMC in aircraft engines. Its principle is to prepare a ceramic coating on the surface of SiCf / SiC CMC components that is resistant to water and oxygen corrosion, molten salt corrosion, and damage from other environmental factors, effectively preventing or slowing down the corrosion and destructive effects of the engine gas environment, and improving the surface stability of ceramic matrix composites in the engine environment. It can be seen that EBCs technology plays a vital role in the research of high-performance advanced engines.
[0003] EBCs are generally composed of a Si bonding layer and a ceramic surface layer. The early first-generation and second-generation ceramic surface layers were based on mullite (3Al2O3·2SiO2, Mullite) and barium strontium aluminum oxide ((1-x)BaO-xSrO-Al2O3-SiO2, 0≤x≤1, BSAS) as the main coating materials, which have excellent thermal, mechanical and chemical compatibility with SiCf / SiC ceramic matrix composites. However, Mullite and BSAS can only meet the service environment below 1200℃. In a higher temperature service environment, they have poor resistance to water vapor corrosion and are prone to instability and peeling. Compared with the first two generations of EBCs, rare earth monosilicates (RE2SiO5, RE=La, Y, Lu, Yb, etc.) have become one of the preferred surface materials for EBCs due to their excellent high temperature resistance, chemical stability, phase stability and environmental corrosion resistance.
[0004] However, the new generation of advanced aero-engines has put forward higher requirements on the performance of SiCf / SiC CMC and EBCs materials. The performance of the existing single rare earth component RE2SiO5 can no longer take into account the high temperature corrosion resistance and low thermal expansion coefficient, and its high temperature corrosion resistance drops sharply with the increase of temperature, which makes it difficult to meet the comprehensive design requirements of the new generation of EBC. In order to develop EBCs with higher service temperature, better resistance to high temperature water oxygen, thermal cycle shock and CMAS corrosion, the current research has expanded from single rare earth main element to new double rare earth main element or multi-rare earth component RE2SiO5 silicate. The cation doping strategy, that is, the use of elements with similar chemical properties to dope, can regulate the thermophysical and chemical properties to a certain extent without changing the crystal structure of the raw materials. It is an effective method to improve the intrinsic performance of the material. Existing research results show that compared with RE2SiO5 with a single rare earth main element, the double rare earth composite RE2SiO5 silicate material prepared by reasonable composition design can show better high temperature phase stability, high temperature water vapor corrosion resistance and CMAS corrosion resistance. Research on the mechanical, thermal and corrosion resistance properties of this type of double rare earth composite RE2SiO5 silicate coating surface material can provide key data accumulation and technical support for the design and development of a new generation of EBCs. At present, the most commonly used methods for preparing double rare earth composite RE2SiO5 silicate powders are mainly solid-phase method, hydrothermal method and sol-gel method. The solid-phase method has too high requirements on equipment and sintering temperature, the particle size of the synthesized powder is large, and insufficient reaction will lead to quality problems such as uneven element distribution and impurities. In addition, the solid-phase method also has problems such as long synthesis cycle, high synthesis temperature, high energy consumption, and low efficiency. The hydrothermal method also has relatively high requirements on equipment and harsh reaction conditions. In summary, it is very necessary to develop a simple and low-cost method for preparing high-quality double rare earth composite RE2SiO5 silicate ceramic powders. The synthesized powders should have the advantages of high purity and uniform element distribution. In view of this, the present invention adopts a sol-gel method to synthesize high-purity composite rare earth (Yb 2-x Y x )SiO5 silicate powder. This method requires simple equipment, simple and controllable process, uniform and sufficient reaction with high purity, small particle size of synthetic powder, and has good application prospects. Summary of the invention
[0005] The technical problem to be solved by the present invention is mainly to overcome the problem in the prior art (Yb 2-x Y x )SiO5 powder generally has problems such as low purity and mismatch between the thermal expansion coefficient of the surface material and the substrate. This paper provides a high-purity composite rare earth monosilicate (Yb 2-x Y x )Preparation method of SiO5 ceramic powder.
[0006] In order to solve the technical problem, the technical solution adopted by the present invention is:
[0007] A method for preparing high-purity composite rare earth monosilicate ceramic powder comprises the following steps:
[0008] S1, the chemical formula of the ceramic powder is (Yb 2-x Y x )SiO5, wherein x=1-2, for example, x can be 0.2, 0.4, 0.6, 0.8, 1. According to the stoichiometric ratio of each element in the chemical formula, ytterbium nitrate pentahydrate, yttrium nitrate hexahydrate and ethyl tetrasilicate are weighed, that is, the molar ratio of ytterbium salt and yttrium salt is (2-x):x, and the molar ratio of the total molar amount of rare earth atoms to the molar amount of Si atoms is (Yb+Y):Si=2:1.
[0009] S2. Add ytterbium nitrate pentahydrate Yb(NO3)3·5H2O and yttrium nitrate hexahydrate Y(NO3)3·6H2O into anhydrous ethanol, heat and stir at a constant temperature of 60-80°C to completely dissolve the two rare earth nitrates in the anhydrous ethanol to obtain a clear mixed solution A, and cool to room temperature.
[0010] S3. Add ethyl tetrasilicate dropwise into the mixed solution A under magnetic stirring, and continue stirring to obtain a clear mixed solution B.
[0011] S4. Dilute 2 mol / L HCl solution with ethanol at a volume ratio of HCl solution to ethanol of 0.3:1; slowly drop the diluted HCl solution into the mixed solution B under magnetic stirring to obtain a clear mixed solution C, seal the solution with plastic wrap, place it in an oil bath at 60-80°C and stir at a constant temperature until a transparent precursor sol is formed, and age it to obtain a non-flowing wet gel.
[0012] S5. Place the wet gel in a constant temperature drying oven for drying until a light yellow dry gel is obtained.
[0013] S6. The dry gel was crushed and ground into fine powder in an agate mortar, and passed through a coarse sieve with a 100-mesh sieve; the sieved gel powder was poured into a corundum crucible, and placed in a high-temperature tube furnace, heated to 1400-1600°C and calcined for 60-120 minutes to obtain high-purity (Yb 2-x Y x )SiO5 powder.
[0014] Preferably, the constant temperature heating and stirring in step S2 is oil bath stirring. By setting the oil bath conditions, the raw materials can be fully reacted. In this technical solution, the oil bath stirring temperature is 60-80°C.
[0015] Preferably, the oil bath stirring time in step S4 is 18-24 hours.
[0016] Preferably, in step S5, the drying is first performed at 80-100° C. for 6-8 h, and then at 120-150° C. for 16-24 h.
[0017] Preferably, the high temperature calcination in step S6 adopts a gradient heating method: first, the temperature is increased from room temperature to 1000°C at a heating rate of 5-10°C / min, then the temperature is increased to 1400-1600°C at a rate of 2-5°C / min and kept for calcination for 60-120min, then the temperature is decreased to 1000°C at a rate of 2-5°C / min, then the temperature is decreased to 300°C at a rate of 5-10°C / min, and finally naturally cooled to room temperature.
[0018] The beneficial effects of the present invention are embodied in:
[0019] The present invention adopts a simple and efficient sol-gel method to synthesize high-purity composite rare earth silicate (Yb 2-x Y x )SiO5 ceramic powder has excellent characteristics such as uniform distribution of rare earth elements and no impurities. By changing the proportion of doping elements, the thermal expansion coefficient and thermal conductivity of the material can be adjusted, and the thermal expansion matching and thermal insulation capacity of SiCf / SiC CMC and coating materials can be improved, providing technical guidance and theoretical support for the high stability and long service life of RE2SiO5 environmental barrier coatings on the hot end components of the engine. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0021] Figure 1 The (Yb prepared in Example 1 of the present invention 1.8 Y 0.2 ) Transmission electron microscope photograph, scanning electron microscope photograph and XRD pattern of SiO5 powder.
[0022] Figure 2 The (Yb prepared in Example 2 of the present invention 1.6 Y 0.4 ) Transmission electron microscope photograph, scanning electron microscope photograph and XRD pattern of SiO5 powder.
[0023] Figure 3 The (Yb prepared in Example 3 of the present invention 1.4 Y 0.6 ) Transmission electron microscope photograph, scanning electron microscope photograph and XRD pattern of SiO5 powder.
[0024] Figure 4 The (Yb prepared in Example 4 of the present invention 1.2 Y 0.8 ) Transmission electron microscope photograph, scanning electron microscope photograph and XRD pattern of SiO5 powder.
[0025] Figure 5 These are the transmission electron microscope photograph, scanning electron microscope photograph and XRD spectrum of the (Yb1Y1)SiO5 powder prepared in Example 5 of the present invention.
[0026] Figure 6 In the embodiment of the present invention, high purity (Yb 2-x Y x )Synthesis flow chart of SiO5 powder.
[0027] Figure 7 (a) Figure 7 (b) and Figure 7 (c) are respectively prepared according to Examples 1-5 of the present invention (Yb 2-x Y x )The curves of heat capacity, thermal diffusion coefficient and thermal conductivity of SiO5 ceramic powder changing with temperature.
[0028] Figure 8 (a) and Figure 8 (b) are respectively prepared according to Examples 1-5 of the present invention (Yb 2-x Y x )The thermal expansion coefficient (ΔL / L0) and thermal expansion coefficient TEC curve of SiO5 ceramic powder changing with temperature. DETAILED DESCRIPTION
[0029] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.
[0030] The following is a description of the preparation of high-purity (Yb 2-x Y x The contents not described in detail in the embodiments of the present invention belong to the prior art known to professionals in the field.
[0031] Example 1
[0032] A sol-gel method for preparing high-purity (Yb 1.8 Y 0.2 ) The method for preparing SiO5 powder comprises the following steps:
[0033] Step S1: The chemical formula of the ceramic powder is (Yb 1.8 Y 0.2 )SiO5, according to the molar ratio of Yb:Y=9:1, (Yb+Y):Si=2:1, weigh 12.127g of ytterbium nitrate pentahydrate (Yb(NO3)3·5H2O), 1.149g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and 3.125g of ethyl tetrasilicate.
[0034] Step S2: put ytterbium nitrate pentahydrate and yttrium nitrate hexahydrate into the same beaker and mix them, then pour 17.7 mL of anhydrous ethanol (analytical grade) into the beaker, and completely dissolve the ytterbium nitrate pentahydrate and yttrium nitrate hexahydrate in the anhydrous ethanol under a 70° C. oil bath and magnetic stirring to obtain a clear mixed solution A, which is then cooled to room temperature.
[0035] Step S3, adding ethyl tetrasilicate dropwise into the mixed solution A under magnetic stirring, and continuously stirring to obtain a clarified mixed solution B.
[0036] Step S4, dilute 2 mol / L HCl solution with ethanol at a volume ratio of HCl solution to ethanol of 0.3:1. Slowly add 0.2 mL of the diluted HCl solution to the mixed solution B under continuous stirring to obtain a clear and transparent mixed solution C, and seal the solution with plastic wrap, and stir at a constant temperature in an oil bath at 70°C for 24 hours to form a transparent precursor sol, which is aged overnight to obtain a wet gel.
[0037] Step S5, the wet gel is first placed in a constant temperature drying oven at 80° C. for drying for 8 hours, and then placed in a constant temperature drying oven at 150° C. for drying for 24 hours to obtain a light yellow dry gel.
[0038] Step S6, the dry gel was fully ground in an agate mortar until there were no agglomerates, then passed through a 100-mesh sieve and placed in a corundum crucible, pushed into a tube furnace, and the temperature was raised from room temperature to 1000°C at a rate of 5°C / min, then raised to 1500°C at a rate of 2°C / min, and kept at that temperature for 60 minutes, then cooled to 1000°C at a rate of 2°C / min, then cooled to 300°C at a rate of 5°C / min, and finally cooled naturally to room temperature, thereby obtaining high-purity (Yb 1.8 Y 0.2 )SiO5 powder.
[0039] The (Yb 1.8 Y 0.2 )SiO5 powder was tested for purity and morphology, and the following results were obtained:
[0040] Figure 1 The (Yb prepared in this example was analyzed by transmission electron microscopy, scanning electron microscopy and X-ray diffraction analyzer.1.8 Y 0.2 ) Transmission electron microscope photos, scanning electron microscope photos and XRD patterns obtained from SiO5 powder testing, among which: Figure 1 (a) is (Yb 1.8 Y 0.2 )TEM images of lattice fringes and diffraction patterns of SiO5 powder; Figure 1 (b) is (Yb 1.8 Y 0.2 ) FE-SEM image of SiO5 powder at a magnification of 10K; Figure 1 (c) is (Yb 1.8 Y 0.2 )SiO5 powder XRD spectrum. TEM image shows that the calcined (Yb 1.8 Y 0.2 )SiO5 particles have obvious lattice stripes and good crystallinity. SEM morphology characterization results show that (Yb 1.8 Y 0.2 )SiO5 grains are equiaxed or nearly elliptical; and by comparison, it can be found that with the increase of Y 3+ As the doping amount gradually increases, the grain size tends to decrease. The diffraction peaks obtained by XRD test correspond one-to-one with the standard PDF card (PDF#40-0386), and there is no second phase diffraction peak, indicating that the powder particles prepared by the sol-gel method are single-phase and have high purity. It can be seen from the PDF card that (Yb 1.8 Y 0.2 The crystal structure of SiO5 ceramic powder is monoclinic, where α=γ=90°, β=102.64°, and the theoretical density is 6.960 g / cm 3 .
[0041] Example 2
[0042] A sol-gel method for preparing high-purity (Yb 1.6 Y 0.4 ) The method for preparing SiO5 powder comprises the following steps:
[0043] Step S1: The chemical formula of the ceramic powder is (Yb 1.6 Y 0.4 )SiO5, according to the molar ratio of Yb:Y=4:1, (Yb+Y):Si=2:1, weigh 10.779g of ytterbium nitrate pentahydrate (Yb(NO3)3·5H2O), 2.298g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and 3.125g of ethyl tetrasilicate.
[0044] Step S2: put ytterbium nitrate pentahydrate and yttrium nitrate hexahydrate into the same beaker and mix them, then pour 17.7 mL of anhydrous ethanol (analytical grade) into the beaker, and completely dissolve the ytterbium nitrate pentahydrate and yttrium nitrate hexahydrate in the anhydrous ethanol under a 70° C. oil bath and magnetic stirring to obtain a clear mixed solution A, which is then cooled to room temperature.
[0045] Step S3, adding ethyl tetrasilicate dropwise into the mixed solution A under magnetic stirring, and continuously stirring to obtain a clarified mixed solution B.
[0046] Step S4, diluting the 2 mol / L HCl solution with ethanol according to a volume ratio of HCl solution to ethanol of 0.3:1.
[0047] Under continuous stirring, 0.2 mL of dilute hydrochloric acid was slowly added to the mixed solution B to obtain a clear and transparent mixed solution C. The solution was sealed with plastic wrap and stirred at a constant temperature of 70° C. in an oil bath for 24 h to form a transparent precursor sol, which was aged overnight to obtain a wet gel.
[0048] Step S5, the wet gel is first placed in a constant temperature drying oven at 80° C. for drying for 8 hours, and then placed in a constant temperature drying oven at 150° C. for drying for 24 hours to obtain a light yellow dry gel.
[0049] Step S6, the dry gel was fully ground in an agate mortar until there were no agglomerates, then passed through a 100-mesh sieve and placed in a corundum crucible, pushed into a tube furnace, and the temperature was raised from room temperature to 1000°C at a rate of 5°C / min, then raised to 1500°C at a rate of 2°C / min, and kept at that temperature for 60 minutes, then cooled to 1000°C at a rate of 2°C / min, then cooled to 300°C at a rate of 5°C / min, and finally cooled naturally to room temperature, thereby obtaining high-purity (Yb 1.6 Y 0.4 )SiO5 powder.
[0050] Figure 2 The (Yb prepared in this example was analyzed by transmission electron microscopy, scanning electron microscopy and X-ray diffraction analyzer. 1.6 Y 0.4 ) Transmission electron microscope photos, scanning electron microscope photos and XRD patterns obtained from SiO5 powder testing, among which: Figure 2 (a) is (Yb 1.6 Y 0.4 )TEM images of lattice fringes and diffraction patterns of SiO5 powder; Figure 2 (b) is (Yb 1.6 Y 0.4 ) FE-SEM image of SiO5 powder at a magnification of 10K; Figure 2 (c) is (Yb 1.6 Y 0.4)SiO5 powder XRD spectrum. TEM image shows that the calcined (Yb 1.6 Y 0.4 )SiO5 particles have obvious lattice stripes and good crystallinity. SEM morphology characterization results show that (Yb 1.6 Y 0.4 )SiO5 grains are equiaxed or nearly elliptical; and by comparison, it can be found that with the increase of Y 3+ As the doping amount gradually increases, the grain size tends to decrease. The diffraction peaks obtained by XRD test correspond one-to-one with the standard PDF card (PDF#40-0386), and there is no second phase diffraction peak, indicating that the powder particles prepared by the sol-gel method are single-phase and have high purity. It can be seen from the PDF card that (Yb 1.6 Y 0.4 The crystal structure of SiO5 ceramic powder is monoclinic, where α=γ=90°, β=102.64°, and the theoretical density is 6.680 g / cm 3 .
[0051] Example 3
[0052] A sol-gel method for preparing high-purity (Yb 1.4 Y 0.6 ) The method for preparing SiO5 powder comprises the following steps:
[0053] Step S1: The chemical formula of the ceramic powder is (Yb 1.4 Y 0.6 )SiO5, according to the molar ratio of Yb:Y=7:3, (Yb+Y):Si=2:1, weigh 9.432g of ytterbium nitrate pentahydrate (Yb(NO3)3·5H2O), 3.447g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and 3.125g of ethyl tetrasilicate.
[0054] Step S2: put ytterbium nitrate pentahydrate and yttrium nitrate hexahydrate into the same beaker and mix them, then pour 17.7 mL of anhydrous ethanol (analytical grade) into the beaker, and completely dissolve the ytterbium nitrate pentahydrate and yttrium nitrate hexahydrate in the anhydrous ethanol under a 70° C. oil bath and magnetic stirring to obtain a clear mixed solution A, which is then cooled to room temperature.
[0055] Step S3, adding ethyl tetrasilicate dropwise into the mixed solution A under magnetic stirring, and continuously stirring to obtain a clarified mixed solution B.
[0056] Step S4, diluting the 2 mol / L HCl solution with ethanol according to a volume ratio of HCl solution to ethanol of 0.3:1.
[0057] Under continuous stirring, 0.2 mL of dilute hydrochloric acid was slowly added to the mixed solution B to obtain a clear and transparent mixed solution C. The solution was sealed with plastic wrap and stirred at a constant temperature of 70° C. in an oil bath for 24 h to form a transparent precursor sol, which was aged overnight to obtain a wet gel.
[0058] Step S5, the wet gel is first placed in a constant temperature drying oven at 80° C. for drying for 8 hours, and then placed in a constant temperature drying oven at 150° C. for drying for 24 hours to obtain a light yellow dry gel.
[0059] Step S6, the dry gel was fully ground in an agate mortar until there were no agglomerates, then passed through a 100-mesh sieve and placed in a corundum crucible, pushed into a tube furnace, and the temperature was raised from room temperature to 1000°C at a rate of 5°C / min, then raised to 1500°C at a rate of 2°C / min, and kept at that temperature for 60 minutes, then cooled to 1000°C at a rate of 2°C / min, then cooled to 300°C at a rate of 5°C / min, and finally cooled naturally to room temperature, thereby obtaining high-purity (Yb 1.4 Y 0.6 )SiO5 powder.
[0060] Figure 3 The (Yb prepared in this example was analyzed by transmission electron microscopy, scanning electron microscopy and X-ray diffraction analyzer. 1.4 Y 0.6 ) Transmission electron microscope photos, scanning electron microscope photos and XRD patterns obtained from SiO5 powder testing, among which: Figure 3 (a) is (Yb 1.4 Y 0.6 )TEM images of lattice fringes and diffraction patterns of SiO5 powder; Figure 3 (b) is (Yb 1.4 Y 0.6 ) FE-SEM image of SiO5 powder at a magnification of 10K; Figure 3 (c) is (Yb 1.4 Y 0.6 )SiO5 powder XRD spectrum. TEM image shows that the calcined (Yb 1.4 Y 0.6 )SiO5 particles have obvious lattice stripes and good crystallinity. SEM morphology characterization results show that (Yb 1.4 Y 0.6 )SiO5 grains are equiaxed or nearly elliptical; and by comparison, it can be found that with the increase of Y 3+ As the doping amount gradually increases, the grain size tends to decrease. The diffraction peaks obtained by XRD test correspond one-to-one with the standard PDF card (PDF#40-0386), and there is no second phase diffraction peak, indicating that the powder particles prepared by the sol-gel method are single-phase and have high purity. It can be seen from the PDF card that (Yb1.4 Y 0.6 The crystal structure of SiO5 ceramic powder is monoclinic, where α=γ=90°, β=102.64°, and the theoretical density is 6.400 g / cm 3 .
[0061] Example 4
[0062] A sol-gel method for preparing high-purity (Yb 1.2 Y 0.8 ) The method for preparing SiO5 powder comprises the following steps:
[0063] Step S1: The chemical formula of the ceramic powder is (Yb 1.2 Y 0.8 )SiO5, according to the molar ratio of Yb:Y=3:2, (Yb+Y):Si=2:1, weigh 8.084g of ytterbium nitrate pentahydrate (Yb(NO3)3·5H2O), 4.596g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and 3.125g of ethyl tetrasilicate.
[0064] Step S2: put ytterbium nitrate pentahydrate and yttrium nitrate hexahydrate into the same beaker and mix them, then pour 17.7 mL of anhydrous ethanol (analytical grade) into the beaker, and completely dissolve the ytterbium nitrate pentahydrate and yttrium nitrate hexahydrate in the anhydrous ethanol under a 70° C. oil bath and magnetic stirring to obtain a clear mixed solution A, which is then cooled to room temperature.
[0065] Step S3, adding ethyl tetrasilicate dropwise into the mixed solution A under magnetic stirring, and continuously stirring to obtain a clarified mixed solution B.
[0066] Step S4, diluting the 2 mol / L HCl solution with ethanol according to a volume ratio of HCl solution to ethanol of 0.3:1.
[0067] Under continuous stirring, 0.2 mL of dilute hydrochloric acid was slowly added to the mixed solution B to obtain a clear and transparent mixed solution C. The solution was sealed with plastic wrap and stirred at a constant temperature of 70° C. in an oil bath for 24 h to form a transparent precursor sol, which was aged overnight to obtain a wet gel.
[0068] Step S5, the wet gel is first placed in a constant temperature drying oven at 80° C. for drying for 8 hours, and then placed in a constant temperature drying oven at 150° C. for drying for 24 hours to obtain a light yellow dry gel.
[0069] Step S6, the dry gel was fully ground in an agate mortar until there were no agglomerates, then passed through a 100-mesh sieve and placed in a corundum crucible, pushed into a constant temperature zone of a tube furnace, and the temperature was raised from room temperature to 1000°C at a rate of 5°C / min, then raised to 1500°C at a rate of 2°C / min, and kept at that temperature for 60 minutes, then cooled to 1000°C at a rate of 2°C / min, then cooled to 300°C at a rate of 5°C / min, and finally cooled naturally to room temperature, thereby obtaining high-purity (Yb 1.2 Y 0.8 )SiO5 powder.
[0070] Figure 4 The (Yb prepared in this example was analyzed by transmission electron microscopy, scanning electron microscopy and X-ray diffraction analyzer. 1.2 Y 0.8 ) Transmission electron microscope photos, scanning electron microscope photos and XRD patterns obtained from SiO5 powder testing, among which: Figure 4 (a) is (Yb 1.2 Y 0.8 )TEM images of lattice fringes and diffraction patterns of SiO5 powder; Figure 4 (b) is (Yb 1.2 Y 0.8 ) FE-SEM image of SiO5 powder at a magnification of 10K; Figure 4 (c) is (Yb 1.2 Y 0.8 )SiO5 powder XRD spectrum. TEM image shows that the calcined (Yb 1.2 Y 0.8 )SiO5 particles have obvious lattice stripes and good crystallinity. SEM morphology characterization results show that (Yb 1.2 Y 0.8 )SiO5 grains are equiaxed or nearly elliptical; and by comparison, it can be found that with the increase of Y 3+ As the doping amount gradually increases, the grain size tends to decrease. The diffraction peaks obtained by XRD test correspond one-to-one with the standard PDF card (PDF#40-0386), and there is no second phase diffraction peak, indicating that the powder particles prepared by the sol-gel method are single-phase and have high purity. It can be seen from the PDF card that (Yb 1.2 Y 0.8 The crystal structure of SiO5 ceramic powder is monoclinic, where α=γ=90°, β=102.65°, and the theoretical density is 6.110 g / cm 3 .
[0071] Example 5
[0072] A method for preparing high-purity (Yb1Y1)SiO5 powder by a sol-gel method comprises the following steps:
[0073] Step S1, the chemical formula of the ceramic powder is (Yb1Y1)SiO5, according to the molar ratio of Yb:Y=1:1, (Yb+Y):Si=2:1, weigh 6.737g of ytterbium nitrate pentahydrate (Yb(NO3)3·5H2O), 5.745g of yttrium nitrate hexahydrate (Y(NO3)3·6H2O) and 3.125g of ethyl tetrasilicate.
[0074] Step S2: put ytterbium nitrate pentahydrate and yttrium nitrate hexahydrate into the same beaker and mix them, then pour 17.7 mL of anhydrous ethanol (analytical grade) into the beaker, and completely dissolve the ytterbium nitrate pentahydrate and yttrium nitrate hexahydrate in the anhydrous ethanol under a 70° C. oil bath and magnetic stirring to obtain a clear mixed solution A, which is then cooled to room temperature.
[0075] Step S3, adding ethyl tetrasilicate dropwise into the mixed solution A under magnetic stirring, and continuously stirring to obtain a clarified mixed solution B.
[0076] Step S4, diluting the 2 mol / L HCl solution with ethanol according to a volume ratio of HCl solution to ethanol of 0.3:1.
[0077] Under continuous stirring, 0.2 mL of dilute hydrochloric acid was slowly added to the mixed solution B to obtain a clear and transparent mixed solution C. The solution was sealed with plastic wrap and stirred at a constant temperature of 70° C. in an oil bath for 24 h to form a transparent precursor sol, which was aged overnight to obtain a wet gel.
[0078] Step S5, the wet gel is first placed in a constant temperature drying oven at 80° C. for drying for 8 hours, and then placed in a constant temperature drying oven at 150° C. for drying for 24 hours to obtain a light yellow dry gel.
[0079] Step S6, the dry gel is fully ground in an agate mortar until there are no agglomerates, then passed through a 100-mesh sieve and loaded into a corundum crucible, pushed into a tubular furnace, and the heating rate is controlled to be 5°C / min from room temperature to 1000°C, then heated to 1500°C at a rate of 2°C / min, and kept warm for 60 minutes, then cooled to 1000°C at a rate of 2°C / min, and then cooled to 300°C at a rate of 5°C / min, and finally naturally cooled to room temperature, thereby obtaining high-purity (Yb1Y1)SiO5 powder.
[0080] Figure 5 The transmission electron microscope photo, scanning electron microscope photo and XRD spectrum of the (Yb1Y1)SiO5 powder prepared in this embodiment are respectively detected by transmission electron microscope, scanning electron microscope and X-ray diffraction analyzer, wherein: Figure 5 (a) is the TEM image of the lattice fringes and diffraction patterns of (Yb1Y1)SiO5 powder; Figure 5(b) is the FE-SEM image of (Yb1Y1)SiO5 powder at a magnification of 10K; Figure 5 (c) is the XRD spectrum of (Yb1Y1)SiO5 powder. The TEM image shows that the calcined (Yb1Y1)SiO5 particles have obvious lattice fringes and good crystallinity. The SEM morphology characterization results show that the (Yb1Y1)SiO5 grains are equiaxed or nearly elliptical; and by comparison, it can be found that with the increase of Y 3+ As the doping amount gradually increases, the grain size tends to decrease. The diffraction peaks obtained by XRD testing correspond one-to-one with the standard PDF card (PDF#40-0386), and there is no second phase diffraction peak, indicating that the powder particles prepared by the sol-gel method are single-phase and have high purity. From the PDF card, it can be seen that the crystal structure of (Yb1Y1)SiO5 ceramic powder is monoclinic, where α=γ=90°, β=102.65°, and the theoretical density is 5.850g / cm 3 .
[0081] The results show that the present invention can prepare high-purity single-phase (Yb) by adjusting the sol formula and preparation process and using the sol-gel method under low temperature (1500°C) atmosphere calcination conditions. 2-x Y x )SiO5 powder. Moreover, the embodiment of the present invention not only has a simple preparation process, does not involve a complicated reaction process, and can be prepared at a low raw material price, but also the prepared (Yb 2-x Y x )SiO5 powder has high purity and can provide a technical basis and commercial potential for large-scale synthesis of environmental barrier coating surface materials.
[0082] Figure 7 (a) and Figure 7 (b) shows the (Yb) prepared in each example 2-x Y x ) The calculated melting point Cp of SiO5 ceramic powder and the measured thermal diffusion coefficient α change with temperature. The relationship between thermal conductivity λ and temperature is given by λ=Cp·α·ρ Figure 7 (a) and Figure 7 (b) is calculated. Figure 7 The thermal diffusion coefficient α of the ceramic powder in (b) shows a trend of first decreasing and then increasing. The thermal conductivity is different for different Y doping ratios.
[0083] Figure 8 (a) and Figure 8 (b) are prepared in each embodiment (Yb 2-x Y x )The thermal expansion coefficient (ΔL / L0) and thermal expansion coefficient TEC of SiO5 ceramic powder vary with temperature. Figure 8In (a), ΔL / L0 is linear in the range of 200℃-1300℃, which is due to the expansion of atomic distance at high temperature. Figure 8 (b) The thermal expansion coefficient TEC increases with the increase of temperature, and the thermal expansion coefficient is different when the Y doping ratio is different.
[0084] It can be seen that by changing the proportion of doping elements, the purpose of regulating the thermal expansion coefficient and thermal conductivity of the material can be achieved, and the thermal expansion matching and thermal insulation capacity of SiCf / SiC CMC and coating materials can be improved, which provides technical guidance and theoretical support for the high stability and long service life of RE2SiO5-based environmental barrier coatings on the hot end components of the engine.
[0085] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing high-purity composite rare earth monosilicate ceramic powder, characterized in that: The steps include: S1, the chemical formula of the ceramic powder is (Yb 2-x Y x )SiO5, wherein x=1-2, weigh ytterbium nitrate pentahydrate, yttrium nitrate hexahydrate and ethyl tetrasilicate according to the stoichiometric ratio of each element in the chemical formula; S2, adding ytterbium nitrate pentahydrate and yttrium nitrate hexahydrate into anhydrous ethanol, heating and stirring at a constant temperature of 60-80° C. to completely dissolve the two rare earth nitrates in the anhydrous ethanol to obtain a clear mixed solution A, and cooling to room temperature; S3, adding ethyl tetrasilicate dropwise to the mixed solution A under magnetic stirring to obtain a clear mixed solution B; S4, diluting 2 mol / L HCl solution with ethanol at a volume ratio of HCl solution to ethanol of 0.3:1; adding the diluted HCl solution dropwise to the mixed solution B under magnetic stirring to obtain a clear mixed solution C, which was sealed and placed in an oil bath at 60-80° C. with constant temperature stirring until a transparent precursor sol was formed, and aged to obtain a wet gel; S5, placing the wet gel into a constant temperature drying oven for drying to obtain a dry gel; S6. The dry gel was crushed and ground into fine powder in an agate mortar and passed through a coarse sieve; the sieved gel powder was placed in a high-temperature tube furnace and heated to 1400-1600°C and calcined for 60-120 minutes to obtain high-purity (Yb 2-x Y x )SiO5 powder.
2. The method for preparing high-purity composite rare earth monosilicate ceramic powder according to claim 1, characterized in that: The ytterbium nitrate pentahydrate, yttrium nitrate hexahydrate and anhydrous ethanol used were of analytical grade, and the ethyl tetrasilicate used was of reagent grade.
3. The method for preparing high-purity composite rare earth monosilicate ceramic powder according to claim 1, characterized in that: The stirring time in the oil bath in step S4 is 18-24 hours.
4. The method for preparing high-purity composite rare earth monosilicate ceramic powder according to claim 1, characterized in that: In step S5, the drying is firstly carried out at 80-100°C for 6-8h, and then at 120-150°C for 16-24h.
5. The method for preparing high-purity composite rare earth monosilicate ceramic powder according to claim 1, characterized in that: The high temperature calcination in step S6 adopts a gradient heating method: first, the temperature is increased from room temperature to 1000°C at a rate of 5-10°C / min, then the temperature is increased to 1400-1600°C at a rate of 2-5°C / min and kept for calcination for 60-120min, then the temperature is decreased to 1000°C at a rate of 2-5°C / min, then the temperature is decreased to 300°C at a rate of 5-10°C / min, and finally naturally cooled to room temperature.
6. A high-purity composite rare earth monosilicate ceramic powder obtained by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Sol-gel process for preparing Yb2SiO5 powder
CN101066764A
Flaky Y2SiO5 preparation method
CN105776232A
Method for synthesizing YSO ceramic powder at low temperature on basis of sol-gel technology
CN106007689A
Preparation method of composite rare earth silicate powder
CN106342076B
Preparation method of high-temperature oxidation-resistant rare earth silicate thermal barrier coating on surface of titanium alloy composite material
CN113025945A
Cited By
Preparation method of rare earth silicate ceramic
CN120349188A
A method for producing a rare-earth silicate ceramic
CN120349188B
Two-component rare earth monosilicate spraying powder with porous structure as well as preparation method and application of two-component rare earth monosilicate spraying powder
CN120483174A